Distribution and ten-year temporal trends (2009–2018) of perfluoroalkyl substances in gull eggs from Spanish breeding colonies. (15th January 2022) - Colomer-Vidal, Pere; Bertolero, Albert; Alcaraz, Carles; Garreta-Lara, Elba; Santos, Francisco Javier; Lacorte, Silvia
Abstract: Gull eggs are excellent bioindicators of environmental pollution as reflect the contamination levels of coastal areas, especially of persistent and bioacumulative compounds such as perfluoroalkyl substances (PFAS). This study aims to evaluate the geographical distribution and 10-year temporal trends (2009–2018) of 17 PFAS in eggs of two gull species ( Larus michahellis and Larus audouinii ) from 5 main Spanish colonies. ∑PFAS ranged from 13.7 ± 5.9 to 164 ± 17 ng g −1 wet weight and higher concentrations were observed in L. audouinii than in L. michahellis . Perfluorooctane sulfonate (PFOS) was the predominant compound in all samples, followed by perfluoroundecanoic acid (PFUnA) and perfluorotridecanoic acid (PFTriDA). Perfluorododecanoic acid (PFDoA), perfluorodecanoic acid (PFDA) and perfluorooctanoic acid (PFNA) were also found in all studied areas but at lower concentrations, while perfluorooctanoic acid (PFOA) was only detected in the Medes Islands. Principal Component Analysis revealed the co-occurrence of the 6 detected PFAS, and differentiated samples from Ebro Delta and Medes Islands, both located in the North-Eastern Mediterranean Sea, with high contribution of all PFAS, from Chafarinas and Atlantic Islands with lower concentration levels and variability. Also, different patterns were observed among colonies, suggesting the fish-based diet plays an important role in PFAS bioaccumulation. In all colonies, except for the Medes Islands, ∑PFAS decreased through the 10-year study period, with PFOS, PFUnA, and PFTriDA showing a significant concentration reduction in a colony-specific manner. This study demonstrates the usefulness and importance of continuous systematic long-term monitoring to determine the geographical distribution and temporal variations of PFAS in marine protected areas using gull eggs as bioindicators of environmental pollution.